User Interface / User Experience Design Aksaranesia.co Mobile Based with Design Thinking Approach - Saputri, Aulia Dwi (Universitas Negeri Surabaya, 2023)
One of the comprehensive problems in SMA Intensif Taruna Pembangunan Surabaya is the lack of integrative literacy activities. Therefore, this study aims to design UI/UX Aksaranesia.co, application as one of the efforts to improve the literacy movement in SMA Intensif Taruna Pembangunan Surabaya. The method used is design thinking with five stages: emphasize, define, design, prototype, and testing. Some of the views or features designed are the design system, onboarding screen, sign-up page, log-in page, dashboard page, interactive features, explore page, library page, class page, and profile page. The application Aksaranesia.co is effective for improving GLS in SMA ITP based on the test results. The Aksaranesia.co application is a stimulus given to students to interpret literacy as an activity that is interesting, fun, and close to technology.